Waste characterization and methane concentration measurement at two waste dumping facilities in the Philippines Quezon City controlled dumping facility and Tanay open dumpsite - Theingi Soe (2010)
Methane is a powerful greenhouse gas contributing to global warming and climate change. Surficial methane concentration was measured using a 1-m open chamber and a Laser Methane Detector (LMD) at the old mound of the Quezon City Controlled Dumping Facility (QCCDF) or popularly known as Payatas, Quezon City and Tanay Open Dumpsite, Rizal Municipality in the Philippines. At the Payatas dumpsite, methane concentration was determined on approximately 50m x 50m grid at Phase I in the period of July -September 2009 and the two transects (50m and 30m) at Phase II in January 2010. At the Tanay Open Dumpsite, methane concentration was measured on the 40 m transect in December 2009 and on the two transects (40m each) in March 2010. From the results of field measurement conducted at the Payatas, four methane hotspots, two in July and two in August were observed with the concentrations of 1839.11, 1436.94, 1333.22, and 777.28 ppm, respectively, at the different points at Phase I while two hotspots, 2704.33 and 1063.33 ppm, were found in January at Phase II. Methane concentration measured at the Tanay Open Dumpsite was significantly lower than that from the Quezon City Controlled Dumping Facility. The spatial variability of methane concentration was evaluated utilizing geostatistics (kriging). Solid waste characteristics were also studied at the Quezon City Controlled Dumping Facility. Buried waste samples taken from three pits with various depths at Phase I were characterized in terms of waste composition, pH, moisture content, temperature, bulk density, particle size, and organic matter content while fresh waste sample was taken and characterized in terms of its composition. The results show that the most common component in buried and fresh waste is plastic, which is nonbiodegradable, followed by the kitchen waste in fresh waste composition.